Analisis Kesalahan dalam Menyelesaikan Soal Operasi Hitung Bilangan Pecahan pada Siswa Kelas VIII SMP - Hamdah; Ilham Minggi; Rismayanti (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2022)
This study aims to describe the errors made by students in solving fractional arithmetic operations based on Kastolan theory. This type of research is a qualitative research with a descriptive approach. Data collection techniques used are tests and interview guidelines. The test is in the form of a description. The test is given to class VIII students at one of the SMP Negeri in the Selayar Island Regency totaling 23 students, then 3 students were taken as research subjects. The criteria for selecting research subjects were to have the most and varied errors. The data analysis technique used is data reduction, data presentation and conclusion drawing. The errors analyzed were categorized using the Kastolan error criteria which consisted of three types of errors. Based on the data from the research and discussion, it can be concluded that students made conceptual errors, procedural errors and technical errors. The most dominant type of error made by students is conceptual error.